Penyuluhan Penyakit Demam Berdarah Dengue (DBD) Pada Masyarakat Di Puskesmas Langsa Timur - Etika Sari; Intan Bahrina; Yusriati Yusriati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Dengue fever is an infectious disease that can cause outbreaks. Dengue fever is a disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito. This disease is a health problem in Indonesia because the disease spreads quickly and can cause death in a short time. The aim of this activity is to provide an explanation about dengue hemorrhagic fever such as how it is transmitted, symptoms and efforts that can be taken to prevent dengue fever. The method of this activity is in the form of counseling. This outreach was considered successful because this outreach activity could increase public knowledge and awareness in preventing dengue fever in the surrounding environment